Clavicle fractures - incidence of supraclavicular nerve injury - Pedro Jose Labronici; Fabio Soares Segall; Bernardo Augusto Martins; Jose Sergio Franco; Gustavo Jose Labronici; Bruno de Araujo Silva; Leonardo Rosa da Rocha (Revista Brasileira de Ortopedia, 2013)
OBJECTIVE: To analyze retrospectively 309 fractures in the clavicle and the relation with injury of the supraclavicular nerve after trauma. METHODS: It was analyzed 309 patients with 312 clavicle fractures. The Edinburgh classification was used. Four patients had fractures in the medial aspect of the clavicle, 33 in the lateral aspect and 272 in the diaphyseal aspect and three bilateral fractures. RESULTS: 255 patients were analyzed and five had paresthesia in the anterior aspect of the thorax. Four patients had type 2 B2 fracture and one type 2 B1 fracture. All patients showed spontaneous improvement, in the mean average of 3 months after the trauma. CONCLUSION: Clavicle fractures and/ or shoulder surgeries can injure the lateral, intermediary or medial branches of the supraclavicular nerve and cause alteration of sensibility in the anterior aspect of the thorax. Knowledge of the anatomy of the nerve branches helps avoid problems in this region.